Pengembangan Interface dan Experience Aplikasi Manajemen Kegiatan Notelife Menggunakan Pendekatan Design Thinking.pdf - Ni Luh Gede Cahaya Putri Mahadewi; I Ketut Gede Suhartana (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
The COVID-19 pandemic has presented major challenges to global productivity, especially for office workers who have switched to Work from Home (WFH). This research focuses on developing the "Notelife" application using a design thought approach to overcome these productivity challenges. The design thinking method is applied through five stages: Empathize, Define, Ideate, Prototype, and Test. The Empathize stage involved interviews with five office workers to understand their management activity needs. The Define stage produces user personas and pain points based on interview results. The Ideate stage creates solution ideas, and the Prototype stage produces the "Notelife" application design including task, file, and time management features. Testing was carried out using the System Usability Scale (SUS) on 20 respondents, and the Notelife application achieved an average SUS value of 82,625, exceeding the average value of 68 for system usability. In conclusion, the design thought approach succeeded in producing a Notelife application design that suits user needs and provides a positive user experience in managing daily activities.